Fluorescent and Magnetic Radical Dendrimers as Potential Bimodal Imaging Probes - Songbai Zhang; Vega Lloveras; Yufei Wu; Juan Tolosa; Joaquín C. García-Martínez; José Vidal-Gancedo (MDPI AG, 2023)
Dual or multimodal imaging probes have emerged as powerful tools that improve detection sensitivity and accuracy in disease diagnosis by imaging techniques. Two imaging techniques that are complementary and do not use ionizing radiation are magnetic resonance imaging (MRI) and optical fluorescence imaging (OFI). Herein, we prepared metal-free organic species based on dendrimers with magnetic and fluorescent properties as proof-of-concept of bimodal probes for potential MRI and OFI applications. We used oligo(styryl)benzene (OSB) dendrimers core that are fluorescent on their own, and TEMPO organic radicals anchored on their surfaces, as the magnetic component. In this way, we synthesized six radical dendrimers and characterized them by FT-IR, 1H NMR, UV-Vis, MALDI-TOF, SEC, EPR, fluorimetry, and in vitro MRI. Importantly, it was demonstrated that the new dendrimers present two properties: on one hand, they are paramagnetic and show the ability to generate contrast by MRI in vitro, and, on the other hand, they also show fluoresce emission. This is a remarkable result since it is one of the very few cases of macromolecules with bimodal magnetic and fluorescent properties using organic radicals as the magnetic probe.